Review on Gandhaka Druti: An Unexplored Herbo-mineral Formulation - Baby, Sangeetham P; Jadar, P G (International Research Journal of Ayurveda & Yoga, 2022)
Gandhaka is a Rasa-dravya that is commonly used in Ayurvedic practice. One of the most unique dosage forms involving Gandhaka is “Gandhaka-druti,” which is a herbo-mineral formulation with an oil base indicated in various diseases. Despite its applicability in different diseases and promising results with minimum dose, the various methods of its preparation and entirety of its indication need to be explored. The present study is an effort to compile different textual references related to the formulation pertaining to its preparation and applicability beyond skin diseases along with recent research updates in order to pave way for the Ayurvedic fraternity to make utmost use of this wonder drug. Through thorough review, 13 different varieties of Gandhaka druti was obtained from different literature and also 8 different studies related to this. Most of the study was based on the popular method and other indications are still unexplored. Furthermore, research based on various indications is required in Ayurveda. The present study has reviewed the scope from the classical texts to emphasize the application of Gandhaka druti in various conditions rather than the skin disorders.